A case of intestinal schwannoma initially suspected by transvaginal ultrasound - Laura López-Marín, MD; Alejandro Olloqui, MD; Ana Villalba, MD; José Manuel Puente, MD, PhD; Alberto Galindo, MD, PhD (Radiology Case Reports, 2022)
Schwannomas are peripheral nerve sheath tumors. Due to their low incidence, few cases of colorectal schwannomas have been published, which increases the diagnostic challenge. The aim of this case report is to discuss the role of transvaginal ultrasound in different areas than the gynecological disorders, when on hands of properly trained professionals that perform systematized procedures. A 56-year-old woman consulted for postmenopausal genital bleeding. During transvaginal ultrasound, a colonic solid, hypervascularized mass of 23 × 26 mm was visualized. As a result of this incidental finding, the patient underwent a sigmoidectomy, with a final diagnosis of intestinal schwannoma. Transvaginal ultrasound is today one of the most useful and accurate diagnostic tools in the assessment of gynecological disorders. However, the proximity of other pelvic structures makes it possible to evaluate the presence of nongynecological conditions. This fact should encourage gynecologists to systematize the transvaginal ultrasound procedure.